Penerapan Metodologi Terpadu pada Rekayasa Proses Akademik Universitas - Gantini, Tiur; Adelia, Adelia; Siboro, Sinta Marito; Sandroto, Indah Victoria (Maranatha University Press, 2025)
Rapid technological developments in the era of globalization require universities to continuously improve their academic systems. When academic systems undergo renewal, related business processes must also be reengineered to align with ongoing activities. This study aims to analyze the effectiveness of integrating four methods—Value Stream Mapping (VSM), Voice of Customer (VOC), Voice of Business (VOB), and Pick Chart—in reengineering academic business processes at a university in Bandung. The research methodology consists of three phases: problem formulation, theoretical review, and business process reengineering design. Data was collected through interviews with stakeholders, including academic staff, lecturers, and students, as well as direct observation of 14 (fourteen) Standard Operating Procedures. The VSM method was used to map the current process and identify problems, VOC captured customer complaints, VOB measured institutional-level problems, and Pick Chart prioritized solutions based on difficulty and impact of implementation. The results of the study show that this integrated framework effectively identifies inefficiencies and proposes targeted improvements. For the grade revision process, the re-engineered business process reduced processing time from approximately one week to 55 (fifty-five) minutes, while eliminating paper waste through the implementation of digital forms. This study concludes that the integration of VSM, VOC, VOB, and Pick Chart provides a comprehensive and systematic framework for re-engineering academic business processes that can be replicated by other higher education institutions.